Seed Yield and Yield Components of Sesame as Affected by Various Weed Control Methods (Bangladesh Agronomy Journal, 2020)
Weed control strategy greatly influences on weed infestation and yield of sesame. An experiment was conducted at Regional Agricultural Research Station, Ishurdi, Pabna during Kharif-1 season of two consecutive years 2015-16 and 2016-17 to find out the suitable weed control methods in sesame. It comprises five weed control methods viz., Application of Panida (T1), Application of Panida with one hand weeding at 20 DAE (T2), One hand weeding at 20 DAE (T3), Two hand weedings at 20 and 40 DAE (T4) and Control (no weeding) (T5 ). The experiment was laid out in a randomized complete block design with three replications. Among the weed species, Cyperus rotundus and Digitaria sangunalis were the most abundant weeds. Application of Panida with one hand weeding at 20 DAE (T2) gave the lowest weed density, weed biomass and the highest weed control efficiency followed by application of Panida (T1) in both years. Weed biomass influenced negatively on plant height, number of capsule plant-1, seed yield and stalk yield. The maximum seed yield and stalk yield were also obtained from T2 which was statistically similar to T1 treatment and the minimum seed yield from T5. Economic analysis indicated that T2 gave higher gross return but T1 provided higher gross margin and benefit cost ratio. The treatment, T4 showed higher total variable cost due to the high cost of labour for hand weeding with the increase of variable cost, which affected the marginal return and benefit-cost ratio. However, based on the economic point of view, application of Panida in pre-emergence condition (T1) was a profitable and suitable weed control method in summer sown sesame.Bangladesh Agron. J. 2020, 23(1): 107-116